Performance Behavior of Corn Smallholders for Sustainable Cooperative Change in West Kalimantan - Nurliza Nurliza; Agus Ruliyansyah; Rini Hazriani (Universitas Muhammadiyah Yogyakarta, 2020)
The production of corn as the second most important cereal crops after rice is dominated by smallholders, particularly in West Kalimantan. However, smallholders in farmer cooperatives are unsustainable because of the lack of decision-making power at the grassroots level; limited access to land, capital, technologies, information and financial services; low market competitiveness; weak management; and limited policy and socio-cultural norms. This research aims to construct the behavior model for performance change of cooperative farmers in Rasau Jaya, Kubu Raya district, West Kalimantan. It involved 75 smallholders recruited using purposive sampling technique. In-depth interviews using the structural equation modeling/SEM based on the new institutional approach and the theory of planned behavior were used in the study. The findings proved that intentions and past behaviors have positive and negative influence on farmers' cooperative behavior, but contradicted with control. Therefore, there are several efforts for changing the behavior in corn farmers’cooperatives, i.e. the perceived behavioral control can stimulate the motivation to be long-lived performing based on the resources and opportunities; pro-environmental behavior needs to engage a supportive injunctive norm and a supportive descriptive norm; a subjective norm for motivation to exhibitthe positive experiential attitude; and the confidence to perform and control their performance.